Comparative mitogenome characterization of cryptic Asian seabass (Lates calcarifer) in captivity within Peninsular Malaysia - Mohd Bakri, Athirah; Esa, Yuzine (Penerbit UTM Press, 2024)
Lates calcarifer is one of the most commercial species in the world. Yet, phylogenetic relationships among this cryptic species remain unclear despite its significance in the fishery sector. The first report on bifurcation of captive Lates calcarifer in Peninsular Malaysia (PM) inferred from complete mitochondrial genome was discussed in the present study. Two mitochondrial genomes (mitogenomes) of Lates species were sequenced and assembled. The mitogenome length was 16,627 bp and 16,515 bp for K4 and S15, respectively. The majority of PCGs in both species exhibited the common initiation marker ATG codon and ended with termination marker TAA codon. Also, the incomplete termination codon T/TA was found in both species. Most AT-skew and GC-skew values observed in the protein-coding genes (PCGs) across the two samples were negative. The phylogenetic analysis based on 13 protein-coding genes by Maximum-Likelihood tree displayed two lineages from different regions which were from Myanmar/Indian waters (K4) and Southeast Asia/ Australian waters (S15). The striking genetic distance values between both specimens indicated 13 PCGs were suffering purifying selection. This study offers significant information for future analyses of evolutionary relationships among the numerous and taxonomically puzzling perciform fishes.